The Effect of Project Based Learning Model on History Learning Interest in Grade XI IPS AT SMAN 1 Baros - Herlina, Lina; Nurhasanah, Ana; Wibowo, Tb Umar Syarif (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to determine the effect of the Project Based Learning Model on interest in learning history in class XI IPS at SMAN 1 Baros. This study uses a quantitative research type with a pre-experimental design approach. The sampling technique used is the probability sampling technique of the simple random sampling type. Data collection in this study used a questionnaire. The results of this study can be seen from the results of a simple regression test which shows a calculated tvalue= 16.154 while ttable= 1.687 with a significance level of 0.05. Because tcount > ttable, the regression has an effect. This means that the application of the Project Based Learning model has an effect on students' interest in learning history. The coefficient of determination is obtained= 0.882. This means that the student's learning interest score is 88.2% influenced by the Project Based Learning model, while the remaining 11.8% is influenced by other factors, such as students' understanding ability, individual cognitive level of each student, and contextual conditions. The implementation of the Project Based Learning model has an effect on the interest in learning history in class XI IPS at SMAN 1 Baros, so it is expected that teachers can develop the learning process using the Project Based Learning model as one of the history learning models at SMAN 1 Baros.